2003
DOI: 10.1016/s1010-7940(03)00119-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of visceral pleura invasion in non-small cell lung cancer

Abstract: We were able to demonstrate that visceral pleura invasion was a factor of poor prognosis in T2 NSCLC. It was found to correlate with more extensive mediastinal lymph node involvement and a decreased survival rates. Therefore, the patients with visceral pleura invasion should be closely followed up especially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 14 publications
2
41
1
2
Order By: Relevance
“…SHIMIZU et al [23] also demonstrated that tumours with a diameter .3 cm had higher frequency of VPI. However, no correlation between tumour size and VPI was found in the report by KANG et al [20]. Our results showed that there was no association between VPI and tumour size in stage IB NSCLC with a diameter .3 cm.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…SHIMIZU et al [23] also demonstrated that tumours with a diameter .3 cm had higher frequency of VPI. However, no correlation between tumour size and VPI was found in the report by KANG et al [20]. Our results showed that there was no association between VPI and tumour size in stage IB NSCLC with a diameter .3 cm.…”
Section: Discussioncontrasting
confidence: 83%
“…JONES et al [4] reported that the frequency of VPI in patients with stage IB NSCLC was 36.4%, while KANG et al [20] reported only 23%. In our study, the frequency of VPI in stage IB NSCLC with a diameter .3 cm was 25.6% (121 out of 472 patients).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations